ANALYSIS ON LISTENING EXERCISES IN LOOK AHEAD 2 (ENGLISH COURSE BOOK FOR SENIOR HIGH SCHOOL STUDENTS YEAR XI) - Muhammad Iqbal (Jurnal Sains Riset, 2019)
The title of this research is â€œAnalysis on Listening Exercises in Look Ahead 2 (English Course Book for Senior High School Students Year XI)â€. The problem of this research can be stated as follow: Are the listening exercises relevance to KTSP curriculum? How the listening exercises in the text book look ahead 2 present items questions?. Its purpose was to find out whether the listening exercise in Look Ahead 2 an English Course for Senior High School Year XI published by Erlangga is relevance with the KTSP curriculum and there are twelve (12) listening exercises which is included in discrete test, 3 listening exercises which is included in communicative test and 1 listening exercises which is included in combination between both. In collecting the data, the writer used in this research is library research, which is a type of study that makes the data library as the theory to study and examine the hypotheses and concepts to obtain to get result that objective. The sample of this research was listening exercise in the text book look ahead 2. Based on the result of this research, the writer found that listening exercise based KTSP curriculum of Senior High School Grade Year XI suitable of competency standard (SK) 2, and basic competency (KD) 2.1 and 2.2. The listening exercise in Look Ahead 2, an English Course for Senior High School Grade Year XI published by Erlangga, show that the higest number of test is discrete test, so it is proper enough in improving of studentâ€™s ability in listening through kind of this test.